An Empirical Study Of Locus Of Control And Cultural Dimensions As Moderating Variables Of The Effect Of Participative Budgeting On Job Performance And Job Satisfaction - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT This study examined relationships between participative budgeting and both job performance and job satisfaction. Of interest were the effects of locus of control and cultural dimensions as possible moderating variables. Prior research found that U S. managers who had an internal locus of control tended to perform better and to be more satisfied when their companies used participative budgeting systems. On the other hand, U. S. managers with an external locus of control tended to perform better and to be more satisfied when non-participative budgeting systems were being used In a later study, however, locus of control did not moderate the effect of participative budgeting on job satisfaction of Mexican managers. This study extended prior research by assessing cultural dimensions as additional moderating variables. Indonesian managers in the Jakarta area were used as subjects